2017
DOI: 10.1016/j.gexplo.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of technologies for remediation of heavy metal contaminated soils

Abstract: , et al.. A comparison of technologies for remediation of heavy metal contaminated soils. Journal of Geochemical Exploration, Elsevier, 2016Elsevier, , 182, pp.247 -268. 10.1016Elsevier, /j.gexplo.2016 Any correspondence concerning this service should be sent to the repository administrator: staff-oatao@listes-diff.inp-toulouse.fr a b s t r a c tSoil contamination with persistent and potentially (eco)toxic heavy metal(loid)s is ubiquitous around the globe. Concentration of these heavy metal(loid)s in soil h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
431
0
35

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,061 publications
(466 citation statements)
references
References 256 publications
(275 reference statements)
0
431
0
35
Order By: Relevance
“…Although various physical and chemical methods have been developed for the removal of heavy metals and metalloids from contaminated substrates, almost all of these methods are expensive and require large investments [2]. By contrast, phytoremediation, a technology that involves the use of…”
Section: Introductionmentioning
confidence: 99%
“…Although various physical and chemical methods have been developed for the removal of heavy metals and metalloids from contaminated substrates, almost all of these methods are expensive and require large investments [2]. By contrast, phytoremediation, a technology that involves the use of…”
Section: Introductionmentioning
confidence: 99%
“…Low Hg concentrations were observed in the leaves and stems and especially in the rhizomes compared with the concentrations in the roots, which indicates that limited transportation of Hg occurs from the root system to other plant tissues (Cattani et al ). Numerous studies have shown that plants are able to assimilate Hg from topsoil into roots through a transpiration stream (Fernandez‐Martinez et al ; Khalid et al ). Because of the low solubility and strong binding between Hg and soil particles, Hg availability for plants is generally very low (Baya and Van Heyst ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the copper and zinc concentrations in soil, herbage, and food were markedly higher in samples from the affected area than those from the control area ( P < 0.01 ). In general, the maximum tolerable concentrations in sheep were 25 and 300 mg/kg, for copper and zinc, respectively [13, 39–40]. Thus, it appears that the heavy metal poisoning of the sheep in the pasture was not related to copper and zinc.…”
Section: Discussionmentioning
confidence: 99%